Pandora. - James, Henry (The Floating Press, 2014)
Many of Henry James' most acclaimed works of fiction are set at the intersection between European and American culture. The novella Pandora takes its tension from the differences between the Old World and the New -- as well as the surprising similarities between the two realms. Free-spirited American Pandora Day crosses paths with the reserved Count Vogelstein, and the two learn a great deal about their respective countries and worldviews.